IDENTIFIKASI KESALAHAN PENYUSUNAN SKRIPSI MINI DALAM MATA KULIAH·PENULISAN KARYA ILMIAH MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN - Sukarmin, Yustinus (Jurnal Cakrawala Pendidikan, 2016)
This research discusses. the mini thesis development process which was conducted by. Sports Science Faculty students· in the Scientific Paper Writing course. The. aim of this research is to· identify the·mistakes made by the students in the mini thesis development. .This research was· a descriptive study on mistakes. The. population consisted of 237 mini theses written by students of the. Faculty of Sports .. Science in the Scientific Paper Writing course in the academic year of 2006/2007. The sample consisted of 100 mini theses selected by using the proportional sampling technique. The data collection instruments were a check-list and a table developed from Pedoman Tugas Akhir UNY 2003 (Thesis Guidelines Yogyakarta State University 2003). The data were analyzed by using the descriptive quantitative technique involving percentage. The results of this research showed that in the mini thesis writing, technically, students made mistakes mostly in grammar, spelling and punctuation, .writing rules, and content. In the writing organization, the most common mistakes were made in the middle part, while the mistakes in the introductory part and those in the closing were evenly balanced.